Estimación de costos para la producción de guayaba rosada (Psidium guajava L.) en el sur de Florida - Edward Evans; Fredy H. Ballen; Jonathan H. Crane; Trent Blare; Victor Contreras; Aditya Singh (EDIS)
Guava is planted thorugh the Tropics and SubTropics and has adapted to a variety of climatic conditions. Florida is the primary producer of guava in the United States. This crop is valued at $3.2 million at the packing house. The growing interest in alternative tropical crops in the last few years has led to increasing interest in this crop. This publication estimates the costs and returns from an established guava orchard in south Florida. We estimate that an established pink guava orchard will have a net return of $9065 per acre per year or $1.13 per pound of fruit sold.